2019
DOI: 10.1108/ics-01-2019-0019
|View full text |Cite
|
Sign up to set email alerts
|

Refining the PoinTER “human firewall” pentesting framework

Abstract: Purpose Penetration tests have become a valuable tool in the cyber security defence strategy in terms of detecting vulnerabilities. Although penetration testing has traditionally focussed on technical aspects, the field has started to realise the importance of the human in the organisation, and the need to ensure that humans are resistant to cyberattacks. To achieve this, some organisations “pentest” their employees, testing their resilience and ability to detect and repel human-targeted attacks. In a previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The summary of literature review is presented in table 1. In our proposed approach we have derived human pentest approach from this research article with title "Refining the PoinTER 'human firewall' pentesting framework" [28] and induced it in adversary emulation process.…”
Section: Related Workmentioning
confidence: 99%
“…The summary of literature review is presented in table 1. In our proposed approach we have derived human pentest approach from this research article with title "Refining the PoinTER 'human firewall' pentesting framework" [28] and induced it in adversary emulation process.…”
Section: Related Workmentioning
confidence: 99%
“…Cyber-attacks' impact on SMEs can be significant regarding financial losses and reputational damage. A study by [4] found that SMEs in the Netherlands lost an average of £65,000 per cyber-attack. Furthermore, the reputational damage caused by a cyber-attack can be particularly damaging for SMEs, as they may struggle to regain the trust of their customers and partners.…”
Section: Introductionmentioning
confidence: 99%